Immigration and two-component unemployment - Max Albert; Jürgen Meckl (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2002)
We analyze the employment effects of immigration within a model that accounts for several stylized facts of the German labor market. The co-existence of positive wage spans and unemployment is explained by wage rigidities that are simultaneously caused by effciency-wage setting and minimum wages. The observed positive relation between wage spans and minimum wages results from employment shifts from low-wage to high-wage sectors. Employment effects of immigration are opposite to those of a rise in the minimum wage. For plausible parameter values, immigration raises employment of the home labor force even if all immigrants find employment.
Keywords: F11; F22; J31; J64; 330; immigration; unemployment; effciency wage; wage drift; wage span; Einwanderung; Beschäftigungseffekt; Theorie der Arbeitslosigkeit; Effizienzlohn; Lohnrigidität; Mehr-Sektoren-Modell; Lohndrift; Theorie